Insight into influence of process parameters on co-pyrolysis interaction between Yulin coal and waste tire via rapid infrared heating. (1st April 2023) - Wen, Yuxin; Liu, Simeng; Fu, Shihao; Wang, Zhiheng; Hu, Haoquan; Jin, Lijun
Highlights: High heating rate was beneficial to the interaction of coal and waste tire. Synergetic effect between coal and waste tire in co-pyrolysis process was clarified. The quantity and quality of pyrolysis oil was improved by co-pyrolysis. Waste tire as hydrogen donor during co-pyrolysis resulted in more high-quality tar. Abstract: Co-pyrolysis of coal and waste tire is an important route to realize their clean and efficient utilization. To study the interaction during co-pyrolysis, the rapid infrared-heated fixed-bed reactor was adapted to explore the effects of heating rate, pyrolysis temperature and mixing ratio on the products distribution, tar quality and compositions during the co-pyrolysis of Yulin coal (YL) and waste tire (WT), and the interaction mechanism was also explored. The results show that heating rate, mixing ratio and pyrolysis temperature exerted the synergistic effect during co-pyrolysis. High heating rate was beneficial to the interaction of coal and waste tire, and the maximum positive synergistic effect of tar production was obtained at the heating rate of 10 °C/s. The content of light tar (boiling point < 360 °C) in co-pyrolysis tar increased gradually with amount of WT added in blends. When the mixing ratio of YL/WT was 1:1, the most remarkable difference between the experimental and calculated contents of light tar in tar suggested obvious positive synergy among the blended samples. In addition, gas production was remarkably suppressed during co-pyrolysis. It is analyzed that H-rich free radicals like H or CH3 produced from the cleavage of aliphatic hydrocarbon chains of WT or other reactions like cyclization stabilize the free radicals from coal pyrolysis and contribute to the improved tar quality and the synergy during co-pyrolysis.